Multimodality in Online Political Discourse: Internet Memes about Scottish Independence - O. A. Blinova (Научный диалог, 2019)
The article is dedicated to the mediation of the possible independence of Scotland in social networks. A multimodal analysis of thematic Internet memes 2014-2016 is carried out as examples of online political discourse. Online political discourse is characterized as an object of linguistic and multimodal analysis. This type of discourse is considered as an uninstitutional kind of political discourse in general, characterized by informality, spontaneity, high speed of response to public challenges and polyphony. The ability of network political discourse to compress information and the estimated interpretation of reflected reality is noted. The concept of inter-discursiveness is considered as one of the genre-forming features of network political discourse in general and Internet memes in particular. The definition of multimodal text as involving the verbal and visual channels of perception, both of which contain key elements of information for decoding the meaning, is given. Various definitions of the Internet meme as a multimodal genre of Internet communication are considered. The analysis of four Internet memes about the independence of Scotland is given. Memes are analyzed for the relationship of verbal and visual component; stylistic characteristics of the text component; strong and weak position of the visual component; sources of precedent and interdiscursive nature of relations between components.